Awareness of the importance of studying the subject Radiologic Physics in a students group enrolled in first year at the study program Professional Medical Radiologist - Preliminary Study - Stanković, Jovan; Kata, (Education and Research in Health Sciences, 2022)
An information on the importance of the Radiology Physics as a basic for understanding of the material to be studied for related subjects was survey in a group of students enrolled at the study group Professional Medical Radiologist (Higher Medical School of Professional Studies at the Academy of Professional Studies Belgrade). Out of a total of 82 enrolled students, 52 responded to the survey (63.5%), of which 36 (69.2%) had previously completed a medical school, 10 (19.2%) a general school and 6 (11.5%) completed other school. Prior enrollment, the largest number of respondents were partially acquainted with the work tasks they should perform after graduation (64%). The same applies to the knowledge of the study program before applying for enrollment. Respondents who did not acquire secondary education in the field of medicine were more informed about the content and program before applying/enrollment than respondents who acquired secondary education in medicine (67% vs. 14%). Awareness about importance of the program of Radiology Physics, before applying/enrollment was similar among all respondents from "unknown" to "known", and the volume and scope of the material was assessed as moderate (in 77%). About 64% of the respondents state that they are satisfied with the achieved pre-examination results, while remaining are partially satisfied.The survey results indicate the place, role and importance of the subject Introduction to Radiological Physics in the study program Professional Medical Radiologist.
Keywords: radiologic physics; professional medical radiologist; survey